A study of patent analysis of LED bicycle light by using modified DEMATEL and life span. (October 2017) - Lin, Zone-Ching; Hong, Guo-En; Cheng, Po-Fan
Highlights: Proposed a modified DEMATEL method for patent analysis of LED bicycle light. Used the ratios of the normalized numerical values for influence level. The causal diagram of LED bicycle light are obtained by modified DEMATEL. Related Patent's life span and activity trend chart of techniques are established. Combined analysis of causal diagram, activity trend chart and life spans. Abstract: The present study proposed a modified decision-making trial and evaluation laboratory (DEMATEL) method. This innovation method involves collecting the repeated or identically defined technical keywords of patent techniques related to light-emitting diode (LED) bicycle light to determine the ratios of the normalized numerical values of these technical keywords by using one technical domain as the primary domain and another as a variable. The values obtained are then converted to mutual influence levels on a scale of 0 to 4, replacing the conventional expert questionnaire. In this study, in accordance with the operational steps of the decision-making trial and evaluation laboratory method, a general relational influence matrix, direct and indirect relationships diagram, and values of centrality (D + R) and causality (D − R) were obtained. A causal diagram was therefore created. The causal diagram was drawn using values of (D + R) and (D − R) as the two axes and facilitated determining the levels of mutual influence between technical domains. In accordance with the proposed modified decision-making trial and evaluation laboratory method, this study collected patents related to LED bicycle light; moreover, the normalized numerical values of key technical, part/component, and function words that appeared in these patents were calculated. Furthermore, clusters of technical and part or component words were defined in accordance with the first-layer technical category. The second-layer technical categories and functional categories were subsequently defined under the first-layer technical categories to establish the technique–function matrix, thereby dividing the techniques related to LED bicycle light into seven main technical domains. This study then analyzed patent life span. Patent life span was calculated using the announcement date of related patents. Finally, this study investigated the development potential of each technical domain of LED bicycle light by conducting a combined analysis of causal diagram obtained by modified DEMATEL method, activity trend chart of techniques, and patent life spans. The proposed patent analysis method and results can serve companies and engineers as references to facilitate developing new patents.